ANTI-CANCER POTENTIAL OF MARINE MICROBES/ MACRO ALGAE DERIVED NATURAL PRODUCTS AS A POTENTIAL THERAPEUTIC AGENT AGAINST ORAL CANCER - VISHWANATHAN, N.; VISWANATHAN, AKSHAYA; VIMAL, S. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Oral cancer, particularly oral squamous cell carcinoma, is a major global health burden with limited treatment options and high recurrence rates. Marine microbes and macroalgae are rich sources of structurally diverse natural products such as polysaccharides, polyketides, alkaloids, and phenolic compounds that exhibit significant anti-cancer activity. These metabolites act through multiple mechanisms including apoptosis induction, inhibition of angiogenesis, and suppression of oncogenic signaling pathways, oxidative stress regulation, and immune modulation. Emerging evidence highlights their potential as novel therapeutic agents against oral cancer, offering opportunities for safer and more effective treatments.